(untitled) (Physical Education, Health and Social Sciences, 2025)
Marriage has been a main concern to the well-being of an individual and in social stability especially in religious and collectivistic communities like Pakistan. Religiosity has been found to be a significant variable that affects marital relationships but there has been a general paucity of empirical research studies on its effects among married students in higher learning institutions. The current research paper sought to investigate how religiosity affects marital adjustment in Pakistani university students who are married. A quantitative research study based on positivism was used, and 152 married students participating in three universities in the Punjab public sector were selected to participate in the study using a structured questionnaire. The SPSS was used in the analysis of data through descriptive statistics, Pearson correlation, Chi-square tests, and ANOVA. The results showed that there was moderate and statistically significant relationship between religiosity and marital adjustment meaning that the higher the religiosity the higher the marital satisfaction and adjustment. The findings also revealed that the role of religiosity in marital adjustment is significant in the various levels of religious commitment. On the whole, the paper emphasizes on religiosity as a significant psychological and social value that contributes to marital harmony and strength among married students. These implications are significant on marital counseling, university support services and future studies on family relationships in religious societies.